Implikasi Pemikiran Blasius Sudarsono terhadap Perkembangan Pernaskahan Nusantara - Deviyanti, Siti (BACA: Jurnal Dokumentasi dan Informasi, 2023)
ABSTRACT Blasius Sudarsono (BS) is a figure in Indonesia in the field of libraries and librarianship who has been active for 50 years. Many of his thoughts are considered to have had a great influence on the development of the world of libraries and documentation in Indonesia. He not only wrote about librarianship, but also other things, one of which was about ancient manuscripts. This research explains the implications of BS's thoughts regarding ancient manuscripts for the development of Indonesian manuscripts today. The research was conducted using descriptive methods and a qualitative approach. Data collection was carried out using document study and literature study techniques. The collected data is then processed using content analysis techniques and the results are presented in the form of a description. Based on the research results, it can be concluded that almost all of BS's main ideas about ancient manuscripts contain implications that have a great influence on the development of Indonesian manuscripts. The results of these implications can be seen in various aspects related to ancient manuscripts, including regulations and the position of ancient manuscripts as national collections that must be protected and preserved. However, there is one BS thought regarding ancient manuscripts that has not yet been realized, namely regarding government regulations that specifically detail the management of ancient manuscripts.   Keywords: Blasius Sudarsono; archipelago manuscript; government regulations; memory of the world; UNESCO   ABSTRAK Blasius Sudarsono (BS) adalah salah satu tokoh pustakawan di Indonesia yang telah berkiprah selama 50 tahun. Banyak pemikirannya yang dinilai sangat berpengaruh terhadap perkembangan dunia perpustakaan, dokumentasi, dan informasi di Indonesia. Ia tidak hanya menulis seputar kepustakawanan, tetapi juga hal lain, salah satunya adalah mengenai naskah kuno. Penelitian ini menjelaskan implikasi pemikiran BS mengenai naskah kuno terhadap perkembangan pernaskahan Nusantara dewasa ini. Penelitian dilakukan dengan metode deskriptif dan pendekatan kualitatif. Pengumpulan data dilakukan dengan teknik studi dokumen dan studi kepustakaan. Data yang terkumpul kemudian diolah dengan teknik analisis isi dan hasilnya disajikan dalam bentuk deskripsi. Berdasarkan hasil penelitian dapat disimpulkan bahwa hampir semua pokok pemikiran BS tentang naskah kuno mengandung implikasi yang sangat berpengaruh terhadap perkembangan pernaskahan Nusantara. Hasil implikasi tersebut dapat terlihat pada berbagai aspek terkait naskah kuno, antara lain regulasi dan kedudukan naskah kuno sebagai koleksi nasional yang harus dilindungi dan dilestarikan. Meskipun demikian, ada satu pemikiran BS tentang naskah kuno yang belum terlihat realisasinya hingga kini, yakni terkait peraturan pemerintah yang secara khusus merincikan pengelolaan naskah kuno.